Change in the definition of personality disorder in transition to ICD-11: A look from clinical and developmental perspectives - Barkauskienė, Rasa; Gaudiešiūtė, Elena; Skabeikytė, Gabrielė (Psichologija, 2021)
The recent body of research reveals fundamental limitations to the categorical concept of a personality disorder that has led researchers to adopt a new personality disorder concept. During the last decade DSM-5 and ICD-11 diagnostic classifications have accepted the dimensional view towards personality pathology. Despite the differences between the two classifications, the joint aspect of both models is the construct of Levels of personality functioning. The construct of personality functioning involves personality (dys)function in the self and interpersonal domains. This two-step conceptualization includes (a) impairments of self and interpersonal functioning, indicating general signs and severity of personality disorder, and (b) pathological personality traits, reflecting ‘stylistic’ differences in the expression of personality disorder. The new conceptualization of personality disorder reflects the innovative multi-theoretical integration of known, empirically-based personality assessment paradigms. The relationship between personality functioning and interpersonal, psychodynamic, and personological paradigms provides the theoretical integrity and empirically-based structure necessary to understand the overall severity of personality pathology. Many methods (interviews, self-assessment scales, and questionnaires) have already been developed for the assessment of personality functioning, and their development will be encouraged by the ICD-11 classification established in 2022. At present, only one instrument has been developed in Lithuania for assessing the level of personality functioning in young people aged 12–18 (Barkauskienė & Skabeikytė, 2020). The empirical data about the validity of this construct and its capability to differentiate between the normal and impaired personality in adults and adolescents provide promising results, but are still accumulating. Research suggests that adolescence is a stage in development when personality pathology can fully unfold and be validly confirmed, which opens up opportunities for early intervention. Although the dimensional personality disorder model needs to further prove its importance, there is already evidence that it is less stigmatizing and returns psychology and personality into the concept of a personality disorder. This review presents changes in the conceptualization of personality disorders by discussing them from both clinical and developmental perspectives and highlighting the results of key research in recent years.